2009
DOI: 10.1016/j.powtec.2008.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fibre optical measurements and discrete element simulations for the study of granulation in a spout fluidized bed

Abstract: Spout fluidized beds are frequently used for the production of granules or particles through granulation. The products find application in a large variety of applications, for example detergents, fertilizers, pharmaceuticals and food. Spout fluidized beds have a number of advantageous properties, such as a high mobility of the particles, which prevents undesired agglomeration and yields excellent heat transfer properties. The particle growth mechanism in a spout fluidized bed as function of particle-droplet in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…Four different scaling approaches and a full scale approach were tested in the simulation of a spout-fluid bed by Banerjee and Agarwal [114]: one based on parcels, one proposed by Glicksman et al [170], one proposed by Link et al [171], and one based on the terminal particle velocity, proposed by the authors. Banerjee and Agarwal [114] found that their method was both the most reliable in reproducing the behaviour of particles and the most efficient in reducing the number of simulated particles, thus optimising the computational time.…”
Section: Definition Of Particlesmentioning
confidence: 99%
“…Four different scaling approaches and a full scale approach were tested in the simulation of a spout-fluid bed by Banerjee and Agarwal [114]: one based on parcels, one proposed by Glicksman et al [170], one proposed by Link et al [171], and one based on the terminal particle velocity, proposed by the authors. Banerjee and Agarwal [114] found that their method was both the most reliable in reproducing the behaviour of particles and the most efficient in reducing the number of simulated particles, thus optimising the computational time.…”
Section: Definition Of Particlesmentioning
confidence: 99%
“…Calibration of a probe is finding a calibration curve with experiments and computations to convert the voltage time series into solids concentration time series [24]. The appropriate calibration method must be suitable for a wide range of solids concentrations from very low concentrations up to the solids concentrations of a packed bed [14]. However, it is difficult to generate a reference suspension of particles with a given concentration, and it is nearly impossible to produce a homogeneous gas-solid flow.…”
Section: Introductionmentioning
confidence: 99%
“…It has been successfully applied in industrial processes including, among others, combustion [2,3], gasification [4][5][6], drying [7] and granulation [8,9]. However, the hydrodynamics of the spout-fluid bed are much more complex than those of the conventional spouted bed, flow characteristics and scale-up cannot be predicted with confidence at this stage of development [10].…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, Link et al [8,9,13,14] studied particle fluxes, flow regimes and granulation process in a rectangular spout-fluid bed, based on a hard-sphere model developed by Hoomans et al [15]. Zhong et al [16] reported a 3D CFD-DEM simulation of gas and solid turbulent flow in a rectangular spout-fluid bed with V-shape base by incorporating a k-e turbulent model and a DEM model (i.e.…”
Section: Introductionmentioning
confidence: 99%